2014
DOI: 10.1007/s00436-014-4025-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification and phylogenetic study of Demodex caprae

Abstract: The DNA barcode has been widely used in species identification and phylogenetic analysis since 2003, but there have been no reports in Demodex. In this study, to obtain an appropriate DNA barcode for Demodex, molecular identification of Demodex caprae based on mitochondrial cox1 was conducted. Firstly, individual adults and eggs of D. caprae were obtained for genomic DNA (gDNA) extraction; Secondly, mitochondrial cox1 fragment was amplified, cloned, and sequenced; Thirdly, cox1 fragments of D. caprae were alig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 35 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…Although rDNA ITS2 and 630-bp mtDNA COI at the 5′ terminal have been used for intra-and interspecies classification and identification in Acari (Zhao et al 2014;Yang et al 2011;Chitimia et al 2009), it is unclear whether the two genes are suitable for intergeneric identification. In the present study, it was confirmed for the first time that rDNA ITS2 can be used not only for intra-and interspecies identification (intraspecific divergences threshold≤5.20 %, interspecific divergences threshold≥6.18 %) but also for interspecies and intergenera identification (interspecific divergences threshold≤14.86 %, intergeneric divergences threshold≥ 15.72 %) with an obvious barcoding gap.…”
Section: Discussionmentioning
confidence: 99%
“…Although rDNA ITS2 and 630-bp mtDNA COI at the 5′ terminal have been used for intra-and interspecies classification and identification in Acari (Zhao et al 2014;Yang et al 2011;Chitimia et al 2009), it is unclear whether the two genes are suitable for intergeneric identification. In the present study, it was confirmed for the first time that rDNA ITS2 can be used not only for intra-and interspecies identification (intraspecific divergences threshold≤5.20 %, interspecific divergences threshold≥6.18 %) but also for interspecies and intergenera identification (interspecific divergences threshold≤14.86 %, intergeneric divergences threshold≥ 15.72 %) with an obvious barcoding gap.…”
Section: Discussionmentioning
confidence: 99%
“…The invasion of this mite affects mainly older animals and those in a poor body condition (38). The identification and molecular analysis of the gen cox 1 have made it possible to consider D. caprae as a separate species, phylogenetically independent of the other species from the genus Demodex (59).…”
Section: Biology and Morphologymentioning
confidence: 99%
“…The sequences obtained can be compared with those deposited in the GenBank database, which makes it possible to differentiate mite species and create phylogenetic maps of them (21,59). …”
Section: Diagnosticsmentioning
confidence: 99%
“…Species of Macrocheles show a relatively small scale of variability in morphological features, and unknown cryptic diversity can always be uncovered using molecular techniques. Molecular techniques have proven highly effective for exploring the phylogenetic relationships and species boundaries of mites (Dabert et al, 2011 ; Li et al, 2010 ; Skoracka et al, 2012 ; Skoracka & Dabert, 2010 ; Yang et al, 2011 ; Zhao et al, 2014 , 2015 ). However, few studies have used molecular information to explore the phylogenetic relationships of macrochelids.…”
Section: Introductionmentioning
confidence: 99%